Testing the functionality of the application made in .NET Core technology on the Raspberry Pi II platform - Sajnóg, Tomasz Piotr; Czerwiński, Dariusz (Journal of Computer Sciences Institute, 2018)
The paper presents the results of functionality analysis of application made in Microsoft .NET Core technology on Raspberry Pi 2 platform. The research was done by implementing applications using libraries provided by Microsoft and developed by .NET Core community. The focus was placed on usage of this technology in the Internet of Things applications. The comparison of the possibility of using Raspberry Pi interfaces in .NET Core, officially supported Python language and popular Node.js technology was made. The performance of these technologies was also compared